La gamificación para mejorar el aprendizaje en Estudios Sociales en séptimo “B”, Escuela de Educación Básica “Miguel Riofrio”, Loja, periodo, 2023 - 2024 - León Chicaiza, Kevin Adrian (2024)
The present research contemplates the use of Gamification to improve learning in Social Studies. In the development of the work, the general objective was to: Determine the impact of gamification in the learning of Social Studies in seventh ̈B ̈, School of Basic Education "Miguel Riofrio", Loja, period, 2023 - 2024. In addition, we considered the specific objectives of: Diagnose the incidence of Social Studies learning based on gamification, propose a gamified alternative proposal for Social Studies learning and evaluate Social Studies learning developed based on gamification. Theoretical exploration was developed as an essential part of the work. In the methodological section, a research work with a mixed approach was found, given the analysis of quantitative and qualitative data. In addition, the type of research was exploratory and descriptive, since the problem was investigated in order to better understand and describe the gamification and learning scenario. As support for the development of the work, the scientific, analytical, synthetic, deductive, inductive and synthetic methods were used. For the development of the work, 22 students and a teacher of the seventh year of the Miguel Riofrio School of Basic Education participated. As part of the research, the students were submitted to a survey, while the teacher was interviewed. Thus, the research had a positive effect on the students, demonstrating the favorable impact that gamification has on integral learning.